Laparoscopic Cholecystectomy in High Risk Cardiac Patient with DM - Rahman, Md Mushfiqur; Shaheen, Shafiul Alam; Munir, Md Mahbubul Hasan; Sardar, Kawsar; Khan, Md Abdus Salam; Chowdhury, AKM Nurnobi; Rahman, M Khalilur; Mondal, Shamiron Kumar; Mitra, Taposh Kumar (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Introduction: Laparoscopic cholecystectomy remains the standardtreatment for cholelithiasis. Everincreasing number of patients with myriad of medical illness is being treated by this technique. However,significant concern prevails among the surgical community regarding its safety in patients with cardiacco-morbidity. Patients with diabetes, significant cardiac dysfunction and multiple co-morbidities wereprospectively evaluated. Patients were assessed by cardiologists and anesthesiologists and laparoscopiccholecystectomy was performed. Results: Patient demographics, details of peri-operative management and post-operative complicationswere studied.Between July 2014 and January 2018, 32 patients (M:F=24:08) with mean age of 55 years(range 36–78) and having significant cardiac dysfunction had undergone laparoscopic cholecystectomy.Of these, 24 patients were in NYHA class-II, while 8 belonged to class-III. Left ventricular ejection fraction,as recorded by transthoracic echocardiography, was20–30% in 08 (25%) patients and 30–40% in the rest24(75%). In addition, 21 (71%) patients had regional wall motion abnormalities, 11 (34%) patients hadcardiomyopathy while 09 (39%)patients had prior cardiac interventions. Following laparoscopiccholecystectomy, hypertension (21), tachyarrhythmia(4) and bradycardia (2) were the commonest eventsencountered.Two patients required dopamine in the immediate postoperative period but all other patientsmade an uneventful recovery. Conclusion: With appropriate cardiological support, laparoscopic cholecystectomy may be safely performedin patients with significant cardiac dysfunction. JBSA 2020; 33(2): 78-84